Solubilization Methods for Paclitaxel and Docetaxel: An Overview - Fariba Pourkarim; Elaheh Rahimpour; Sima Alvani; Abolghasem Jouyban (Tabriz University of Medical Sciences, 2022)
Cancer is still a serious disease with high incidence over the past decades. Many anticancer drugs are discovered and used to treat cancer, among them, taxanes such as paclitaxel and docetaxel have high lipophilicity and low aqueous solubility which is further magnified considering the strong need for administering them by intravenous infusion. Currently, the poor water-solubility of taxanes is improved by prodrug formation, conjugation, inclusion complexation, micellar solubilization and liposome-based formulations. Recent achievements for solubilization of taxanes are reviewed and critically discussed regarding their pharmaceutical and chemical applications.